2019
DOI: 10.3389/fbioe.2019.00363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Functionalization, and Bioapplications of Two-Dimensional Boron Nitride Nanomaterials

Abstract: Two-dimensional boron nitride nanostructures (2D-BNNs) have been increasingly investigated for their applications in several scientific and technological areas. This considerable interest is due to their unique physicochemical properties, which include high hydrophobicity, heat and electrical insulation, resistance to oxidation, antioxidation capacity, thermal conductivity, high chemical stability, mechanical strength, and hydrogen storage capacity. They are also used as fillers, antibacterial agents, protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Therefore, cells were exposed to different concentrations (20, 40, 80, 160 mg/L) of both commercial BN-PW and BN-PL samples for a period of 24 h. As shown in Figure 6 , after the A549 cells exposure to BN-PW and BN-PL, the viability of the cells was not reduced in the presence of any of the concentrations tested, indicating the absence of cytotoxicity in the employed conditions. Although BN nanomaterials are generally considered highly biocompatible [ 12 ], recent reports suggest that the toxicity of 2D BN depends on the cell type exposed, dosage, and nanomaterial aspect ratio. For instance, Liu et al observed that human hepatoma HepG2 cells viability was significantly reduced in the presence of 30 mg/L BN sheet-like structured nanoparticles [ 24 ], while BN nanosheets changed from non-toxic to toxic towards SaOS2 cells when their diameter was reduced from the micro to nanometer range [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, cells were exposed to different concentrations (20, 40, 80, 160 mg/L) of both commercial BN-PW and BN-PL samples for a period of 24 h. As shown in Figure 6 , after the A549 cells exposure to BN-PW and BN-PL, the viability of the cells was not reduced in the presence of any of the concentrations tested, indicating the absence of cytotoxicity in the employed conditions. Although BN nanomaterials are generally considered highly biocompatible [ 12 ], recent reports suggest that the toxicity of 2D BN depends on the cell type exposed, dosage, and nanomaterial aspect ratio. For instance, Liu et al observed that human hepatoma HepG2 cells viability was significantly reduced in the presence of 30 mg/L BN sheet-like structured nanoparticles [ 24 ], while BN nanosheets changed from non-toxic to toxic towards SaOS2 cells when their diameter was reduced from the micro to nanometer range [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, BN-based nanomaterials have also raised the attention of the scientific community for their possible use in pharmaceutical and medical applications, such as cosmetics, drug delivery, scaffold materials for tissue engineering, and regenerative medicine, etc. [ 12 ]. As a consequence of the growth in the variety of applications of these nanomaterials, the increase of environmental and human exposure will be also higher, and may occur through multiple different pathways, which makes it necessary to study their potential toxicological effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…hBN layers have a AA’ stacking configuration bonded by van der Waals (VdW) forces (with interlayer distance of 3.33 Å) ( Wang et al, 2017 ). Having analogous structure but insulating electrical behavior, hBN is sometimes referred to as “white graphene.” hBN features properties such as high hydrophobicity, thermal insulation, electrical insulation, low dielectric constant, resistance to oxidation, high chemical stability, and mechanical strength ( Mahvash et al, 2017 ; Chilkoor et al, 2018 ; Merlo et al, 2018 ; Emanet et al, 2019 ; Mukheem et al, 2019 ). Due to these properties, 2D BN-based materials have also demonstrated potential in antibacterial coatings ( Mukheem et al, 2019 ), as well as applications in the biomedical field – such as wound healing ( Şen et al, 2019 ), and bone tissue regeneration ( Şen et al, 2019 ; Aki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This becomes particularly important in 2D nanomaterials whose integration into devices and tailoring of properties are controlled via surface modification. In the case of BNs, some functional strategies have been realized to modify their surface, including hydroxyl (-OH), alkoxy (-OR), amino (-NH 2 ), and alkyl (-R) groups [1,28,29]. Compared with other surface functionalization, hydroxylation is the most important functionalization route for modifications of BN materials.…”
Section: Introductionmentioning
confidence: 99%